Case Study of Bengkulu District Court Decision Number 14/Pdt.G/2023/Pn Bgl Dated September 27, 2023 - Apriyanti Apriyanti; Tjempaka Tjempaka (PT Publikasiku Academic Solution, 2023)
Ownership of land for houses is generally freehold. Mastery over. The property rights are proven by the Certificate of Property Rights issued by the National Land Agency (BPN). In ancient times, some people did not understand the legalization of ownership of land rights. The transfer of ownership rights to land can be done in various ways, one of which is buying and selling. Buying and selling transactions are one of the transactions that are very well known in traditional and modern society. Not everyone understands and realizes the need when carrying out sales and purchase transactions on land must be legalized by the authorities so that the transactions that occur are carried out under the hands. Bengkulu District Court Decision Number 14/Pdt.G/2023/PN Bgl dated September 27, 2023, namely land transactions that occur by the Buyer buying from the Seller for Rp. 2,000,000 (two million rupiah) based on the Certificate of Rights Disclosure dated December 11, 1989, at the time of the certificate transaction not yet in the name of the Seller, this can be seen from the certificate issued in 1994 while the transaction has been carried out in 1989. After the sale and purchase transaction was carried out, the Buyer had controlled land with an area of approximately 660 M2 (six hundred and sixty square meters) located in Bengkulu City. Due to the Buyer's ignorance and/or negligence towards the sale and purchase of the land, a Deed of Sale and Purchase has not been made, while at this time the Buyer wants to process the change in the Seller's certificate, its existence is not found. So because there is no legal legitimacy, the validity of the owner of the land needs to get a decision from the Court